Chosen aspects of municipal transport operation on the example of the city of Lublin - Niewczas, Andrzej; Koszalka, Grzegorz; Wrona, Jan; Pieniak, Daniel (Transport, 2008)
The paper presents some aspects of operation of municipal transport system in the city of Lublin (Poland). Organization of Lublin Municipal Transport Company was described, its efficiency and perspectives of development. Particular attention was paid to the rules of adjustment to the EU requirements, and to the influence of demographic and social factors. Infrastructure of public transport in Lublin was analyzed (busses, trolley‐busses, bus stations, fixed objects and bus stops), as well as configuration of bus and trolley‐bus lines. Some specific proposals were also put forward regarding development solutions: development plan of trolley‐bus traction, plan of inter‐connection bus station, development plan of bus traction, introduction of advanced IT solutions into the public transport management and natural gas (CNG) fuelling of the city busses. Keywords: urban transport, urban transport problems.First published online: 27 Oct 2010